2021
DOI: 10.1007/s40519-021-01116-5
|View full text |Cite
|
Sign up to set email alerts
|

Eating disorders during COVID-19 pandemic: the experience of Italian healthcare providers

Abstract: Purpose Due to COVID-19 pandemic, the Italian population lived in quarantine from March to May 2020 (lockdown phase I). Restrictions impacted individuals' psychological health, especially in those with eating disorders (ED). Healthcare providers (HCPs) treating ED provided assistance by telemedicine and/or in walk-in clinics. We hypothesize that social restrictions represented a great stressor for ED patients and HCPs, negatively impacted their therapeutic alliance, and affected the frequency of dysfunctional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 12 publications
3
29
1
Order By: Relevance
“…Due to earlier discharges and/or virtual support, clinicians in both settings recognised the pandemic had shifted responsibility for recovery more towards patients and already burdened carers [ 7 ]. This shift appeared most notable in DP settings and corroborates research into Italian clinicians’ perspectives—virtual support may afford greater opportunity to foster patients’ autonomous motivation and more collaborative treatment [ 8 ], which have been associated with a greater reduction in ED behaviours [ 31 ]. DP, compared to IP, treatment appears to better facilitate responsibility in recovery [ 11 , 32 ], thus, virtual support may further increase this opportunity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Due to earlier discharges and/or virtual support, clinicians in both settings recognised the pandemic had shifted responsibility for recovery more towards patients and already burdened carers [ 7 ]. This shift appeared most notable in DP settings and corroborates research into Italian clinicians’ perspectives—virtual support may afford greater opportunity to foster patients’ autonomous motivation and more collaborative treatment [ 8 ], which have been associated with a greater reduction in ED behaviours [ 31 ]. DP, compared to IP, treatment appears to better facilitate responsibility in recovery [ 11 , 32 ], thus, virtual support may further increase this opportunity.…”
Section: Discussionsupporting
confidence: 69%
“…Limited research has considered clinicians’ experiences of the pandemic, with most focusing on the patient and/or carer perspective [ 5 – 7 ]. To date, clinicians’ experiences of delivering ED treatment during the pandemic have been explored in a service evaluation of a young person’s ED service [ 3 ] and in an online survey of clinicians working in ED services in the initial stages (March–May 2020) of the pandemic [ 8 ]. These studies suggest COVID-19 has significantly impacted ED service delivery.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of participants who reported that the pandemic had worsened specific symptoms was as follows: binge eating (14–47%), dietary restriction (44–65%), driven exercise (42–50%), compensatory behaviors (7–36%), and body image concerns (29–80%). One study surveyed healthcare providers, asking them to retrospectively recall the perceived impact of the pandemic on their patients' symptoms (Colleluori et al, 2021 ). Healthcare providers reported that >30% of their patients had experienced an increase in binge eating and compensatory behaviors during this period.…”
Section: Resultsmentioning
confidence: 99%
“…A systematic literature review conducted by Mehta [ 20 ] including cross sectional and longitudinal studies, concluded the majority of individuals with pre-existing eating disorders reported an increase in anorexic symptomatology. This was also the perception for 41% of health care providers) for adults with AN, [ 21 ].…”
Section: Introductionmentioning
confidence: 75%